Scrunitizing Social Presence of In-Service EFL Teachers’ Instruction in The Enactment Of Blended Learning - Nasrullah, Nasrullah; Rosalina, Elsa; Mariani, Nanik; Rezma Sari, Annisa; Alfisah, Mutiara; Rahmadina, Nida; Ainah, Noor (International Journal of Educational Research & Social Sciences, 2024)
Technology utilization learning is gaining popularity especially when online learning is conducted during and after the worldwide pandemic. Many studies have examined blended learning as an effort to integrate online learning and face-to-face learning which has an impact on increasing student engagement, improving learning outcomes, and providing a more flexible and personalized educational experience. However, the results of previous research also reported that the application of online learning has minimal interaction, thus leading to less meaningful learning. To respond to these problems, this study aims to investigate perceptions about the application of social presence in English teaching in the implementation of blended learning. The results of this study show that quantitatively English teachers have applied 3 important aspects of social presence, of which 59.82% agreed with teaching activities based on affective categories. Followed by the second position, which strongly agrees with 39.50% and disagrees with the application as much as 0.69%. In the Open Communication category, as many as 62.37% of English teachers also agreed with the implementation of this activity, 34.72% strongly agreed, and as many as 3% expressed disapproval. Meanwhile, on the concept of group cohesion, as many as 64.63% agreed, and 35.37% strongly agreed with this concept.